2021
DOI: 10.1089/aut.2020.0083
|View full text |Cite
|
Sign up to set email alerts
|

“Masking Is Life”: Experiences of Masking in Autistic and Nonautistic Adults

Abstract: Background: Autistic masking is an emerging research area, and so far, research has suggested that masking has a negative effect on autistic people. Masking relates to general social practices (such as identity management) and is often driven by stigma avoidance. Many nonautistic people also experience stigma that might drive them to suppress aspects of their identity. In this study, we investigate similarities and differences in experiences of masking in autistic and nonautistic people. Methods: We conducted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 39 publications
6
70
0
3
Order By: Relevance
“…and "automatic", resonating with experiences of autistic adults in other qualitative studies (Bradley et al, 2021;Cage & Troxell-Whitman, 2019;Miller et al, 2021). Many of our participants viewed this as an adaptive change from their earlier much more pressurising and taxing camouflaging efforts.…”
Section: Camouflaging Became More "Integrated" To An Autistic Adult's Self-identity Over Timesupporting
confidence: 66%
See 2 more Smart Citations
“…and "automatic", resonating with experiences of autistic adults in other qualitative studies (Bradley et al, 2021;Cage & Troxell-Whitman, 2019;Miller et al, 2021). Many of our participants viewed this as an adaptive change from their earlier much more pressurising and taxing camouflaging efforts.…”
Section: Camouflaging Became More "Integrated" To An Autistic Adult's Self-identity Over Timesupporting
confidence: 66%
“…However, some autistic adults may not experience automatisation of camouflaging behaviours and may instead find it a constant struggle to know how to camouflage and do so successfully Livingston et al, 2019). Camouflaging may even become increasingly difficult with age (Miller et al, 2021), and some autistic individuals may have a reduced capacity to camouflage due to experiences of autistic burnout from accumulated life stressors (Higgins et al, 2021;Raymaker et al, 2020). Alternatively, for those who are able to camouflage automatically and unconsciously, this could potentially lead to a loss of sense of self when their 'masked' and true selves become so intricately intertwined with one another (Miller et al, 2021).…”
Section: Camouflaging Became More "Integrated" To An Autistic Adult's Self-identity Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Cage et al (2018) also argue that social stigma against Autism contributes to anxiety and depression and creates significant pressure to mask and camouflage. Drawing upon sociologist Goffman's work on stigma, Pearson and Rose (2021;see also Milton, 2013;Sasson et al, 2017) found that Neurotypical stigma against visible Autistic behaviours is a social driver of Autistic masking, while Miller et al (2021) describes masking as a stigma response to minority group status.…”
Section: Scholarly Background: Towards a Minority Group Model Of Neur...mentioning
confidence: 99%
“…The suppression of a native response in favour of a non-native response is known as masking (Milton and Sims, 2016;Holliday-Willey, 2014;Pearson and Rose, 2021), camouflaging (Hull et al 2017), compensation (Livingston and Happé, 2017), concealment (Botha & Frost, 2020), and adaptive morphing (Lawson, 2020). Autistic people have reported that masking of a distress response to aversive sensory stimuli, and suppressing associated coping mechanisms such as stimming, have a negative impact (Kapp et al, 2019;Miller, Rees and Pearson, 2021). This is only one aspect of the broader deleterious effects masking has upon Autistic wellbeing (Mandy, 2019).…”
Section: Maskingmentioning
confidence: 99%